Evidence for a curvilinear dose-response relationship between avoidance coping and drug use problems among women who experience intimate partner violence. - Weiss, Nicole H; Duke, Aaron A; Sullivan, Tami P (Anxiety, stress, and coping, 2014)
Women who experience intimate partner violence (IPV) are at heightened risk for drug use problems. While prevailing models of drug use suggest that IPV-exposed women use drugs in an effort to escape or avoid negative affect, a dearth of literature has examined the role of avoidance coping in drug use problems within this population. Given recent suggestions that flexible, situationally appropriate use of avoidance coping may be adaptive, particularly when confronted with highly stressful situations, we hypothesized that avoidance coping and drug use problems would demonstrate a curvilinear, U-shaped dose-response relationship. Participants were 147 community-recruited women experiencing IPV. Consistent with our hypotheses, moderate levels of avoidance coping were associated with lower levels of drug use problems, whereas high and low levels of avoidance coping were associated with higher levels of drug use problems. Findings highlight the complex relationship between avoidance coping and drug use problems and suggest that avoidance coping, when used in moderation, may be an adaptive strategy for coping with relational conflict among women who experience IPV.
Keywords: Adaptation, Psychological; Adolescent; Adult; Avoidance Learning; Domestic Violence; Female; Humans; Interpersonal Relations; Middle Aged; Risk Factors; Sexual Partners; Spouse Abuse; Substance-Related Disorders; Young Adult